Minimum-Order Observers for hybrid Wind Turbine and Fuel cell - B. Jaganathan (Bulletin of Electrical Engineering and Informatics, 2012)
Renewable Energy Sources are the upcoming energy sources, for they are readily available. The performance of these sources depends upon the available input. A continuous monitoring of the output which is also dependent upon the state variables of the source model (state model) is necessary. It thus, necessitates the incorporation of an observer in the existing system which estimates the state variables continuously. This paper proposes a novel method of design at the design of a minimum order observer for a wind turbine, which further feeds a PMSG. This observer estimates the state variables of the wind turbine and compares this with the state variables of the actual plant model. This in turn generates a control vector which further provides the necessary control actions so that the output of the wind turbine is optimized to an acceptable extent. Three different configurations are made use for the simulation. The plant model with a PI controller in series with it, under open loop,the plant model in its closed loop form with negative feedback and finally the plant with the designed minimum order observer are simulated. It has been observed that the response of the overall system is improved with the implementation of the observer and so does the stability.Matlab/Simulink is used for validating the proposed idea.